The Meaning of the Poverty Definition in Determining the Poverty Line - Chmielewski, Piotr (Journal of Finance and Financial Law, 2016)
The article reviews main approaches to the definition and measurement of poverty. It argues the definition of poverty does matter for poverty eradication strategies and has different implications for targeting beneficiaries. Author of this article underline that monetary definition of poverty line is not sufficient and it should be strengthen by concepts of capability, social exclusion and participatory approaches. The purpose of this article is to show that poverty is a complex and multidimensional phenomenon that can not be describe only by monetary factors.